2020
DOI: 10.3389/fneur.2020.581346
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Frascati-Criteria-Based HIV-Associated Neurocognitive Disorder (HAND) in HIV-Infected Adults: A Systematic Review and Meta-Analysis

Abstract: Background: The HIV associated mortality is decreasing in most countries due to the widespread use of antiretroviral therapy. However, HIV-associated neurocognitive disorder (HAND) remains a problematic issue that lowers the quality of life and increases the public health burden among people living with HIV. The prevalence of HAND varies across studies and selected samples. Therefore, we aimed to quantitatively summarize the pooled prevalence of Frascati-criteria-based HAND and to explore the potential demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 46 publications
3
87
2
1
Order By: Relevance
“…This is consistent with Al-khindi et al (2011) and Habib et al (2013) reviews, which showed modest and substantial ART benefits in people living with HIV, respectively. However, this contrasts with recent studies that have shown no association between ART use and neurocognitive performance (Walker & Brown, 2018;Wei et al, 2020).…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…This is consistent with Al-khindi et al (2011) and Habib et al (2013) reviews, which showed modest and substantial ART benefits in people living with HIV, respectively. However, this contrasts with recent studies that have shown no association between ART use and neurocognitive performance (Walker & Brown, 2018;Wei et al, 2020).…”
Section: Discussioncontrasting
confidence: 83%
“…The global prevalence of HIV-associated neurocognitive impairment in the antiretroviral era is estimated at 43-45% (Wang et al, 2020;Wei et al, 2020). Varying prevalence rates have been reported in studies conducted in low-and middleincome countries in the range of 12-74% (Michael et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, examples such as HIV-associated neurocognitive dysfunction, which afflicts over 40% of people with chronic HIV infection [65], impairing learning, memory, attention, and executive function, suggests possible overlap across multiple chronic viral infections. A recent study in Nature illustrates how such higher order disruptions may be mediated on a molecular level through viral-associated perturbations in general cellular functions such as cortical excitatory synaptic signalling, choroid plexus disruption enabling peripheral T cell infiltration, and promotion of pathological microglial and astrocyte subpopulations [66].…”
Section: Comparison With Previous Empirical Studiesmentioning
confidence: 99%